Estimation of heterosis and combining ability for improving yield, sweetness, carotenoid and antioxidant qualities in pumpkin hybrids (Cucurbita moschata Duch. Ex Poir.) - Hosen, Monir; Rafii, Mohd Y.; Mazlan, Norida; Jusoh, Mashitah; Chwdhury, Mst. Farhana Nazneen; Yusuff, Oladosu; Ridzuan, Raihana; Karim, K. M. Rezaul; Halidu, Jamilu; Ikbal, Mohammad Ferdous (Multidisciplinary Digital Publishing Institute, 2022)
A full diallel mating design was used to hybridize seven pumpkin inbred parental lines, yielding 42 F1 hybrids, including reciprocals. The generated F1 hybrids, parental lines and commercial check hybrid were evaluated in two environments to investigate the per se performances, combining ability effects and magnitude of heterosis over mid-parent, better-parent and commercial check hybrids for yield, yield attributed, sweetness, total carotenoid and antioxidant traits, using a randomized complete block design with three replications. The analysis of variance for most of the examined traits revealed highly significant differences (p ≤ 0.01) for GCA, SCA, reciprocal, maternal and non-maternal variances and their interaction with the environment. Since the inheritance of yield and its contributing fruit quality, and antioxidant traits is governed by non-additive gene action, it suggests heterosis breeding would be useful in obtaining further improvements in pumpkin. From the experiment, it was found that the paternal lines P1 (Gold Butter 315) for dry matter content and DPPH (%), P4 (Asian pumpkin) for total carotenoid content, P6 (Sarawak) for fruit number per plant and P7 (Australia-1) for single fruit weight, fruit flesh thickness, yield per plant and total soluble solid were shown to be good general combiners. In respect to per se performance, combining ability effects and magnitude of heterosis over mid-parent, better-parent and commercial check, the cross P2 (928 Fuxiang) × P1 (Gold Butter 315) and P4 (Asian pumpkin) × P5 (Sarawak) for single fruit weight and yield per plant, the cross P5 (Sarawak) × P2 (928 Fuxiang) for fruits number per plant, P1 (Gold Butter 315) × P7 (Australia-1) and P1 (Gold Butter 315) × P6 (Sarawak) for total soluble solid and dry matter content, P7 (Australia-1) × P2 (928 Fuxiang) for total carotenoid content and P3 (Ser Bajadi) × P1 (Gold Butter 315) for DPPH (antioxidant) were identified to be highly significant positive specific combiners and the highest performers, and these crosses may be exploited as commercial hybrids.